Ambientes especialistas no apoio a produção e gestão de jogos digitais - Martins, Rafael Oliveira (2014)
Define a plataform for game development and your respectives tools is a complex and challenge task nowadays. This work consist in a expert system development capable to organize a game project based on user input (academic or professional), fo cusing on three main areas: development engines and platforms, programming and project management. The main goal is validated beginning with a knowledge database, including existing platforms and business rules with researches and current market data.